Index Premium Trends Resulting from Composition Changes to the S&P 500 and Its Implications for Market Efficiency - nie, dongfang (Journal of Accounting, Business and Management (JABM), 2024)
Transient price pressures immediately before the announcement events and afterward indicate that there is a violation of market efficiency. This paper empirically investigates the state of the market efficiency by following a procedure outlined by Petajisto who looked at trends in index premium and cumulative abnormal returns from 1990 to 2005. This paper provides an update on index premiums and its implications from 2004 to 2012. For additions and deletions to the S&P 500, we find that the cumulative abnormal return from announcement to effective day has averaged 3.98 % and -9.90%. The index premium has varied from 0.05% in 2011 to a peak of 36.2% in 2008, with an average of 4.5% from 2004 to 2012. We claim that index premium and Cumulative Abnormal Return for additions has decreased in the long run. We also claim that the deletions have a stronger impact on the index premium than the additions.